Macroeconomic and health care aspects of the coronavirus epidemic: EU, US and global perspectives - Paul J. J. Welfens (International Economics and Economic Policy, 2020)
The novel coronavirus (COVID-19) epidemic represents a major challenge for the world economy. While a detailed longer-term diffusion path of the new virus cannot be anticipated for individual countries, one may anticipate international supply shocks and declining GDP growth in many OECD countries and China in 2020; and one should expect falling asset prices in Asia, the United States and the European Union plus the United Kingdom – except for the price of risk-free government bonds. In the course of 2020/21 the US, the EU and the UK, as well as other countries, will face both an increasing number of infected patients as well as a higher case fatality ratio. Health care expenditures in the US could increase more than in the Eurozone and the EU in the medium term, a development that undermines the international competitiveness of the United States. The analysis suggests that per capita income is a positive function of the effective trade openness and of the new Global Health Security Index indicator from the NTI/Johns Hopkins University. A rising health care-GDP ratio in the US is equivalent to a rising US export tariff. As regards the coronavirus challenge, the ratio of acute care beds to the elderly in OECD countries shows considerable variation. Due to international tourism contraction alone, output growth in the Eurozone, the US and China can be expected to fall by about 1.6% in 2020. The COVID-19 challenge for the US Trump Administration is a serious one, since the lack of experts in the Administration will become more apparent in such a systemic stress situation – and this might well affect the November 2020 US presidential election which, in turn, would itself have considerable impacts on the UK and the EU27 as well as EU-UK trade negotiations. Integrating the health care sector into macroeconomics, which should include growth analysis, is an important task. The role of health quality - and health insurance coverage - for endogenous time horizons and economic welfare, respectively, is emphasized.
Keywords: I11; I18; F01; H51; 330; Coronavirus; Health system; Macroeconomics; EU; US; China